Effect of Graphene Oxide Addition on Spark Ignition Engine Performance and Cycle-to-cycle Variation with Gasoline-ethanol Fuel - Askar Adika Agama; Ahmad Syihan Auzani; Alfian Ferdiansyah Madsuha; Hendra Hermawan; Ade Kurniawan; Mokhtar Mokhtar; Aswin Aswin; Nasruddin Nasruddin; Yulianto Sulistyo Nugroho; Harinaldi Harinaldi (Universitas Muhammadiyah Magelang, 2026)
A fuel blend of gasoline and ethanol increases octane, meets air quality standards, and satisfies renewable fuel mandates, but the blend does not always result in perfect bonding, causing fuel separation and increasing cyclic variation. To overcome these limitations, up to 60 ppm graphene oxide (GO) nanoparticles were added into an 80:20 gasoline-ethanol blend (E20) and tested for the first time on a spark-ignition (SI) engine. The engine performance was evaluated by measuring cyclic variation, combustion stability and pressure, torque and power, specific fuel consumption, and CO2 emission. The acquired data were then statistically treated by using a coefficient of variation (COV) and then evaluated with Response Surface Methodology (RSM) in order to demonstrate a strong ability to accurately predict the optimization. Results show that the addition of GO nanoparticles into the E20 reduced the COV by up to 19.54% at an engine speed of 8000 rpm when compared to E20 alone, while the torque and power both increased by 5% at 5500 rpm. The specific fuel consumption of the GO-E20 blend was up to 15% higher than that of E20, with a decrease in CO emission but an increase in CO2 emission. Generally, the E20GO blend positively impacts the SI engine’s cyclic stability and performance, but its potential adverse effects on the environment and health must be carefully considered.